Active physiotherapy interventions following total knee arthroplasty in the hospital and inpatient rehabilitation settings: a systematic review and meta-analysis. Issue 1 (March 2018) - Henderson, Kate G.; Wallis, Jason A.; Snowdon, David A.
Abstract: Background: Physiotherapy is a routine component of postoperative management following total knee arthroplasty (TKA). As the demand for surgery increases it is vital that postoperative physiotherapy interventions are effective and efficient. Objectives: Determine the most beneficial active physiotherapy interventions in acute hospital and inpatient rehabilitation for improving pain, activity, range of motion and reducing length of stay for adults who have undergone TKA. Data sources: Electronic databases MEDLINE, CINAHL, PUBMED and EMBASE. Study eligibility criteria: Randomised controlled trials investigating the effect of active physiotherapy interventions in the acute hospital or inpatient rehabilitation setting for adults who have undergone TKA. Study appraisal and synthesis methods: Risk of bias for individual studies was assessed using the Physiotherapy Evidence Database (PEDro) scale. Standardised Mean Differences (SMD) or Mean Differences (MD) and 95% confidence intervals were calculated and combined in meta-analyses. Quality of meta-analyses was assessed using the Grades of Research, Assessment, Development and Evaluation approach. Results: Accelerated physiotherapy regimens were effective for reducing acute hospital length of stay (MD −3.50 days, 95% CI −5.70 to −1.30). Technology-assisted physiotherapy did not show any difference for activity (SMD −0.34, 95% CI −0.82 to 0.13). From high quality individual studies pain, activity and range of motion improved with accelerated physiotherapy regimens and activity improved with hydrotherapy. Limitations: Lack of blinding and small sample sizes across the included trials. Conclusion: After TKA, there is low level evidence that accelerated physiotherapy regimens can reduce acute hospital length of stay. Systematic review registration number PROSPERO (Registration number CRD42014013414)http://www.crd.york.ac.uk/PROSPERO .